Um ofício polivalente: Rodolfo Garcia e a escrita da história (1932-1945) - Brönstrup, Gabriela D'Avila [UNESP] (2015)
Comprehending the métier fundamentals of Rodolfo Augusto de Amorim Garcia (1873-1949), especially, about the own issues on his writing of history, his collecting, selecting and disclosing procedures of historic documents, even as on collection organization, between 1932 and 1945, is the main question of this dissertation. Taking in account the tension between erudite and intellectual figure at that period, some concerns pervade the investigation about the relationships established on the main sociability and production places of knowledge where he has been: What activities did the so-called erudite develop? Which were the motivations of those who referred Rodolfo Garcia as intellectual? Such inquiries will be used as conducting wire in investigation about the possibilities of writing of life by means of correspondences and forewords, as well as his dedication on history knowledge validation by methodical proceedings used in documental edition and promoting specialization courses during a period of investments on professional formation